Positronium probes free volume to identify para- and meta-aramid fibers and correlation with mechanical strength. (17th January 2018) - Ramani, R.; Kotresh, T.M.; Indu Shekar, R.; Sanal, F.; Singh, U.K.; Renjith, R.; Amarendra, G.
Abstract: We adopt here a novel approach to identify the para- and meta- aramid fibers using the available free volume in them. Positron Annihilation Lifetime Spectroscopy (PALS) has been employed to characterize the free volume in these fibers. The free volume content in the para- variety (Kevlar) is less and the free volume distribution is narrow as compared to its meta- counterpart (Nomex). The results are further validated by characterizing the free volume content in Nomex IIIA fibers, which is a blend composed mainly of para- and meta- aramid fibers. The free volume results are in good correlation with the mechanical properties of these fibers obtained by Universal Testing Machine (UTM), structural studies by X-ray diffraction (XRD) and storage modulus using Dynamic Mechanical Thermal Analysis (DMTA). The thermal decomposition temperature (Td ) of the fibers is characterized by thermo gravimetric analysis (TGA). We also show here the first results of an appreciable glass transition temperature (Tg ) not only for the Nomex fibers but also for its blend Nomex IIIA using the combined results of Differential Scanning Calorimetry (DSC) and DMTA. Graphical abstract: Highlights: Free volume content is more in meta- as compared to para- armid fibers. Free volume can be used as a tool to distinguish para- and meta- aramid fibers. Free volume in aramid fibers correlates well with their mechanical properties. Appreciable Tg is found for PMIA fiber and its blend N-IIIA.